Sport Modalities, Performance and Health - Marín, Diego Muñoz; Parraca, José Alberto Frade Martins; Sánchez-Alcaraz Martínez, Bernardino Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sport modalities are highly practiced in order to improve many aspects of human beings, including performance and health. The increasing interest in the quantitative and qualitative aspects of sport training is ascribable to the fact that several training systems and new methodologies are appearing in all sport modalities. These methodologies can have different effects on the organism depending on the degree of training.On the other hand, some of the main objectives in sport research are to describe match activity and to detect effective performance indicators. A better knowledge of players' performance adaptations and game dynamics during competition is extremely useful for optimizing the training process. The need to develop training methodologies according to actions occurring during the game is essential for each sport.